2013
DOI: 10.1159/000353650
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Added Value of Intermittent Photic Stimulation and Hyperventilation in Routine EEG Practice

Abstract: Objective: Investigate the added value of hyperventilation (HV) and intermittent photic stimulation (IPS) to the routine electroencephalogram (EEG). Method: This is a retrospective review of 1,172 successive EEGs. The records with evidence of epileptogenic activity were identified and further analyzed to identify if the activation techniques could trigger the expression of epileptic activity not seen otherwise in the nonactivated tracing. Results: Activation procedures provided additional information in 9.5% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
(32 reference statements)
4
15
1
Order By: Relevance
“…This might result in EEG changes, such as physiological slowing, IRDA/IRTA, or epileptiform activity (Siddiqui et al, 2011 ; Barker et al, 2012 ). Interictal epileptiform activity was found particularly in patients with generalized epilepsy, but also in patients with focal epilepsy (Ahdab and Riachi, 2014 ; Kane et al, 2014 ). The role of EEG changes in patients without epileptic seizures is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…This might result in EEG changes, such as physiological slowing, IRDA/IRTA, or epileptiform activity (Siddiqui et al, 2011 ; Barker et al, 2012 ). Interictal epileptiform activity was found particularly in patients with generalized epilepsy, but also in patients with focal epilepsy (Ahdab and Riachi, 2014 ; Kane et al, 2014 ). The role of EEG changes in patients without epileptic seizures is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Even though some studies have reported that HV can be more effective in female patients 18,28 , our findings were inconclusive. The number of women with abnormalities or seizures during HV was higher than the number of men, but this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 84%
“…Hyperventilation is the oldest provocation methods, its efficiency in triggering absence seizures being observed even before the use of EEG, while the effect it has on cerebral electric activity has been observed by Berger in 1934 and further studied by Gibbs et al in 1935. [15][16][17] Over time, its diagnostic value has been certified by several studies and it has become a part of most standard EEG recordings [16][17][18][19][20][21][22][23][24][25] and it is also of use in intracranial EEG recordings 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that HV has added information in very few patients, Ahdab and Riachi 21 described that only 8 patients out of 1172 did the HV add additional information.…”
Section: Discussionmentioning
confidence: 97%